Ursodeoxycholic acid and lithocholic acid exert anti-inflammatory actions in the colon - Ward, Joseph B. J.; Lajczak, Natalia K.; Kelly, Orlaith B.; O’Dwyer, Aoife M.; Giddam, Ashwini K.; Ní Gabhann, Joan; Franco, Placido; Tambuwala, Murtaza M.; Jefferies, Caroline A.; Keely, Simon; Roda, Aldo; Keely, Stephen J. (American journal of physiology: Gastrointestinal and liver physiology, 2017)
Inflammatory bowel diseases (IBD) comprise a group of common and debilitating chronic intestinal disorders for which currently available therapies are often unsatisfactory. The naturally occurring secondary bile acid, ursodeoxycholic acid (UDCA), has well-established anti-inflammatory and cytoprotective actions and may therefore be effective in treating IBD. We aimed to investigate regulation of colonic inflammatory responses by UDCA and to determine the potential impact of bacterial metabolism on its therapeutic actions. The anti-inflammatory efficacy of UDCA, a nonmetabolizable analog, 6α-methyl-UDCA (6-MUDCA), and its primary colonic metabolite lithocholic acid (LCA) was assessed in the murine dextran sodium sulfate (DSS) model of mucosal injury. The effects of bile acids on cytokine (TNF-α, IL-6, Il-1β, and IFN-γ) release from cultured colonic epithelial cells and mouse colonic tissue in vivo were investigated. Luminal bile acids were measured by gas chromatography-mass spectrometry. UDCA attenuated release of proinflammatory cytokines from colonic epithelial cells in vitro and was protective against the development of colonic inflammation in vivo. In contrast, although 6-MUDCA mimicked the effects of UDCA on epithelial cytokine release in vitro, it was ineffective in preventing inflammation in the DSS model. In UDCA-treated mice, LCA became the most common colonic bile acid. Finally, LCA treatment more potently inhibited epithelial cytokine release and protected against DSS-induced mucosal inflammation than did UDCA. These studies identify a new role for the primary metabolite of UDCA, LCA, in preventing colonic inflammation and suggest that microbial metabolism of UDCA is necessary for the full expression of its protective actions. NEW & NOTEWORTHY On the basis of its cytoprotective and anti-inflammatory actions, the secondary bile acid ursodeoxycholic acid (UDCA) has well-established uses in both traditional and Western medicine. We identify a new role for the primary metabolite of UDCA, lithocholic acid, as a potent inhibitor of intestinal inflammatory responses, and we present data to suggest that microbial metabolism of UDCA is necessary for the full expression of its protective effects against colonic inflammation.